Penyuluhan Massage Effleurage Dalam Menurunkan Nyeri Persalinan Menggunakan Media Poster - Nurul, Nurul Hidayah Bohari; Haerani; Sulymbona, Nurdewi; Agustina, Rika; Akhfar, Kurniati (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2025)
Pain in the first stage of labor arises from cervical dilation and uterine contractions. Pain occurs in the back, sacrum, cramps, and thighs when the fetal head descends into the pelvis, causing pressure on the lumbosacral plexus. Severe pain during labor can cause the mother to experience stress or fear and excessive fear, physiologically this can cause uterine contractions to feel more painful and the pain felt by the mother to increase. Labor pain can be controlled with the non-pharmacological method of Effleurage Massage. This massage aims to increase blood circulation, apply pressure, and warm the abdominal muscles as well as increase physical and mental relaxation. The solutions offered are 1. Increasing pregnant women's understanding of effleurage messages can reduce normal labor pain. The target output of this PKM activity is a scientific article published in an ISSN journal. The method used in implementing this activity includes counseling for pregnant women using poster media. The counseling material consists of the definition of effleurage messages, the benefits of effleurage messages, and techniques. The results showed that education using posters about effleurage massage proved effective in increasing mothers' knowledge and preparedness for the labor process, thereby reducing labor pain.